Millennial-scale phase relationships between ice-core and Mediterranean marine records: insights from high-precision 40Ar/39Ar dating of the Green Tuff of Pantelleria, Sicily Strait - Scaillet, Stéphane; Vita-Scaillet, Grazia; Rotolo, Silvio G. (Quaternary Science Reviews, 2013)
International audience With the advent of annually-resolved polar ice records extending back to 70 ka, marine and continental paleoclimate studies have now matured into a discipline where high-quality age control is essential for putting on an equal pace layer-counted timescale models and Late Quaternary sedimentary records. High-resolution U-Th dating of speleothem records and 40Ar/39Ar dating of globally recorded geomagnetic excursions have recently improved the time calibration of Quaternary archives, reflecting the cross-disciplinary effort made to synchronize the geologic record at the millennial scale. Yet, tie-points with such an absolute age control remain scarce for paleoclimatic time-series extending beyond the radiocarbon timescale, most notably in the marine record. Far-travelled tephra layers recorded both onland and offshore provide an alternative in such instance to synchronize continental and marine archives via high-resolution 40Ar/39Ar dating of the parent volcanic eruption. High-resolution 40Ar/39Ar data are reported herein for one such volcanic marker, the Green Tuff of Pantelleria and its Y-6 tephra equivalent recorded throughout the Central and Eastern Mediterranean. Published radiochronometric and δ18O orbitally-tied ages for this marker horizon scatter widely from about 41 ka up to 56 ka. Our new 40Ar/39Ar age at 45.7 ± 1.0 ka (2σ) reveals that previous estimates are biased by more than their reported errors would suggest, including recent orbital tuning of marine records hosting the tephra bed that are reevaluated in the context of this study. This improved estimate enables potential phase lags and leads to be studied between deep-sea and terrestrial archives with unrivaled (near-millennial) 40Ar/39Ar precision in the marine record.